2007
DOI: 10.1200/jco.2007.25.18_suppl.7535
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for elderly advanced stage non-small cell lung cancer (NSCLC) patients (pts) treated with bevacizumab (B) in combination with carboplatin (C) and paclitaxel (P): Analysis of Eastern Cooperative Oncology Group (ECOG) 4599 study

Abstract: 7535 Background: PC administered in combination with bevacizumab extends survival for advanced non-squamous NSCLC pts. Based on SEER data, elderly pts (age ≥70 years) represent >50% of all new cases of lung cancer and present unique therapeutic challenges. The ECOG 4599 database was analyzed to compare the outcomes in elderly pts treated with PCB vs. PC alone. Methods: Pts ≥ 70 years at study entry constituted the elderly cohort. Each arm (PCB vs. PC) and age group (≥70 vs. <70) was compared with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The addition of bevacizumab to standard chemotherapy led to an increased response rate in both the elderly (29% vs. 17%) and younger patients (36% vs. 14%). 89 However, although this translated into an improved median survival time within the younger group (12.8 vs. 9.6 months; P = .0027), no improvement occurred in the elderly group (12.1 vs. 11.3 months; P = .4).…”
Section: Novel Agents On the Horizonmentioning
confidence: 94%
“…The addition of bevacizumab to standard chemotherapy led to an increased response rate in both the elderly (29% vs. 17%) and younger patients (36% vs. 14%). 89 However, although this translated into an improved median survival time within the younger group (12.8 vs. 9.6 months; P = .0027), no improvement occurred in the elderly group (12.1 vs. 11.3 months; P = .4).…”
Section: Novel Agents On the Horizonmentioning
confidence: 94%
“…43 Another recent ad hoc subset analysis of this trial also found no obvious survival advantage in the 224 elderly ( 70 years of age) patients enrolled in this trial, possibly related to the increased incidence of severe toxicities with bevacizumab, including treatment-related deaths (seven vs two deaths). 44 The benefit observed with bevacizumab in the ECOG 4599 trial came with an increased incidence of neutropenia, hypertension, proteinuria, bleeding events, and treatment-related deaths (15 vs two deaths). Five patients receiving bevacizumab died from hemoptysis, and five additional patients died from complications of neutropenic fever (compared with zero deaths and one death, respectively, in those treated without bevacizumab).…”
Section: Agents Targeting the Vascular Endothelial Growth Factor Pathwaymentioning
confidence: 99%
“…7 Arguments have also been raised against the drug in the elderly, but analysis of both E4599 and AVAiL elderly subsets have shown safety and efficacy in older patients with NSCLC and age alone should not be an exclusion criterion for the drug. 8,9 Based on the enthusiasm with bevacizumab, other similar drugs are in development including other antibodies (ramucirumab), novel constructs (aflibercept), endostatin and a large group of oral tyrosine kinase inhibitors. Although definitive proof of activity is largely still lacking from these newer agents, results to date have been very promising with several of them, strengthening the evidence in support of antiangiogenesis therapy.…”
Section: Heather Wakelee MDmentioning
confidence: 99%
“…A subgroup analysis of ECOG 4599 confirmed that, in elderly patients, bevacizumab was associated with a higher degree of toxicity but no improvement in overall survival. 8 Bevacizumab is expensive. Lung cancer now accounts for more than 20% of cancer deaths and the use of cancer drugs is spiralling out of control.…”
Section: Siow Ming Lee Phd Frcpmentioning
confidence: 99%